IMPLEMENTASI SOFTWARE BASED ROUTER PADA LINGKUNGAN VIRTUALISASI - Marcel, Marcel (Teknik dan Ilmu Komputer, 2012)
Virtualization technology has changed our view on how computation resources being used. This paper discusses how virtualization technology can be used to solve several limitations related to the software-based router using MikroTik RouterOS. Our experiment using hosted-model virtualization shows that virtualization technology can increase the flexibility on how software-based router can be implemented.ÃÂ Keywords:ÃÂ MikroTik RouterOS, virtualization, software-based router